Impact of home literacy environment on literacy development of children with hearing loss: A mediation model - Wang, Qianqian; Ma, Minjie; Huang, Yan; Wang, Xichen; Wang, Tingzhao (Frontiers in Psychology, 2022)
Reading presents an unsolved difficulty for children with hearing loss and research on factors influencing their literacy development is very limited. This work aimed to study the influence of home literacy environment (HLE) on literacy development of children with hearing loss and explore possible mediating effects of reading interest and parent-child relationship. 112 Chinese children with hearing loss were surveyed for scales of HLE, literacy development, reading interest, and parent-child relationship. Result analysis showed that HLE significantly predicted literacy development of children with hearing loss and this effect was no longer significant after including reading interest and parent-child relationship as variables. Further, HLE significantly predicted reading interest and parent-child relationship, each of which predicted literacy development and played a significant mediating role in HLE’s influence on literacy development. These findings provide educational tips for families of children with hearing loss.